Pendampingan Pembelajaran Taman Pendidikan Al-Qur’an Berbasis Aset Lokal untuk Penguatan Edukasi Interaktif dan Pembinaan Tajwid Muyassar - Zainur Arifin; Mohammad Syamsul Muarif; Farhan Masrury; Siti Haifa Fathimatuz Zahro (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study is motivated by the low quality of Qur’anic learning in Taman Pendidikan Al-Qur’an (TPQ), particularly in terms of learning interactivity and students’ mastery of tajwid. In addition, local assets within the TPQ environment have not been optimally utilized to support the learning process. Therefore, this study aims to analyze the implementation of a local asset-based learning assistance model integrated with interactive education and tajwid muyassar guidance. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that local asset-based assistance enhances student participation and engagement through more contextual and interactive learning. The implementation of interactive educational strategies transforms the learning pattern from teacher-centered to participatory. Meanwhile, tajwid muyassar guidance proves effective in improving students’ fashāhah from 16.7% to 73.3%, understanding of tajwid theory from 50% to 80%, and practical application of tajwid from 18.2% to 76.4%. These findings confirm that the integration of a local asset-based approach, interactive education, and tajwid muyassar constitutes an effective model for improving the quality of Qur’anic learning. Overall, this study contributes to the development of adaptive, participatory, and sustainable TPQ learning models.